IMPLEMENTASI MANAJEMEN SISTEM PENILAIAN PEMBELAJARAN SECARA DARING (Studi Kasus di SMA Negeri 1 Cilacap) - Aljihad, Fuad; Sulastini, Rita; Handayani, Sri (Jurnal Tawadhu, 2021)
The use of the internet in the implementation and reporting of learning (e-raport) has not been utilized. The application of e-report at the SMA level is only around 1,400 out of a total of 13,000 SMA in Indonesia. SMAN 1 Cilacap is one of the schools that has used the internet in its assessment and reporting. The use of IT is carried out by applying the management principles of G.R. Terry, are planning, organizing, implementing, and supervising the reporting of student learning outcomes. At all stages carried out together with the hope that there is no school. As a result, 2015 IT was used for UNBK. Since 2019, daily assessments, assignments, midterms, end of semester (sumative), school exams, and national exams have been carried out using the Office 365 applications, Google Classroom, and Mobile Apps, as well as the e-report application in reporting parental learning outcomes. Constraints faced are human resources and technical aspects that can be overcome with assistance by the IT team together with teachers. In practice, technical problems usually occur at the beginning of use.